2020
DOI: 10.1007/s10198-020-01217-5
|View full text |Cite
|
Sign up to set email alerts
|

Cost and effects of integrated care: a systematic literature review and meta-analysis

Abstract: Background Health and care services are becoming increasingly strained and healthcare authorities worldwide are investing in integrated care in the hope of delivering higher-quality services while containing costs. The cost-effectiveness of integrated care, however, remains unclear. This systematic review and meta-analysis aims to appraise current economic evaluations of integrated care and assesses the impact on outcomes and costs. Methods CINAHL, DARE, EMBASE, Medline/PubMed, NHS EED, OECD Library, Scopus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(101 citation statements)
references
References 86 publications
1
83
0
2
Order By: Relevance
“…The economic findings were unexpected based on the findings of previous research [ 37 ], but evaluations of integrated care (IC) programmes come with challenges that have been acknowledged in other contexts. Most integrated care programmes are highly variable in terms of programme components and delivery, making cost comparisons elusive [ 1 37 ]. Kadu et al’s [ 38 ] systematic review of the quality of economic evaluations in IC found that few programmes reported cost reductions.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The economic findings were unexpected based on the findings of previous research [ 37 ], but evaluations of integrated care (IC) programmes come with challenges that have been acknowledged in other contexts. Most integrated care programmes are highly variable in terms of programme components and delivery, making cost comparisons elusive [ 1 37 ]. Kadu et al’s [ 38 ] systematic review of the quality of economic evaluations in IC found that few programmes reported cost reductions.…”
Section: Discussionmentioning
confidence: 92%
“…Instead, the issue was insufficient implementation time, due to a longer than anticipated patient recruitment period, delaying implementation of the full suite of programme components. Other researchers have also found that the cost effectiveness of programmes is typically linked to having sufficient follow-up time to show the impact of IC models [ 4 37 38 46 ]. Bardsley et al [ 47 ] evaluated eight UK programmes and found few cost savings, suggesting a need for longer follow-up to show economic responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Following evidence-based guidelines for patients with multiple chronic conditions, which schemes such as pay-for-performance encourage adherence to, may result in adverse drug and care interactions (Boyd et al , 2005; Marengoni and Onder, 2015). The integrated care models which have been most successful to date are longer-term and disease management models for single conditions (Rocks et al , 2020), which might, in fact, have negative effects for multimorbid patients. Another relevant area of the literature to consider is multitasking (Holmstrom and Milgrom, 1991) when some conditions are not included in the schemes.…”
Section: Discussionmentioning
confidence: 99%
“… * We were to reassess and focus on cost comparisons in the broader roll out of the project in the second phase, but the project was terminated early. A recent meta-analysis serves as a useful guide in the cost analysis of integrated care projects [ 19 ]. …”
Section: Methodsmentioning
confidence: 99%
“…First person experiences of study PCP * We were to reassess and focus on cost comparisons in the broader roll out of the project in the second phase, but the project was terminated early. A recent meta-analysis serves as a useful guide in the cost analysis of integrated care projects [19]. patients to be those of low urgency/acuity, self-referred, presenting for a new episode of care (i.e.…”
Section: Experiences Pre-and Postinterventionmentioning
confidence: 99%